Cak Nur dan Liberalisasi Islam:Nalar Pembaruan Pemikiran Islam Nurcholish Madjid - Muhammad Sahlan; Dendy Wahyu Anugrah (AL-Ikhtiar : Jurnal Studi Islam, 2026)
So far, the idea of reforming Islamic thought put forward by Nurcholish Madjid is still being studied as an intellectual movement that has a significant influence on the development of Islamic thought in Indonesia. So that the concept of thought renewal initiated by Nurcholish Madjid (Cak Nur) tends to be only described descriptively, without further reviewing how the reason used in demonstrating the renewal of Islamic thought. Therefore, this article wants to analyze the reasoning position of Cak Nur's Islamic thought reform which is sourced from the paper "The Necessity of Islamic Thought Reform and the Problem of Integration of the Ummah" (1970). The research method used is literature study (library research) with a philosophical-textual approach. Then, to identify the position of Cak Nur's reasoning, the researcher used the epistemology of Muhammad Abid al-Jabiri's reasoning. Finally, this article comes to the conclusion that the reason used by Cak Nur in the project of reforming Islamic thought is more inclined to the reason of burhani. Because, in the update, Cak Nur offers a liberalization of thought that includes secularization, freedom of thought, ideas of progress and an open attitude. Abstrak Selama ini gagasan pembaruan pemikiran Islam yang dikemukakan Nurcholish Madjid masih ditelaah sebagai sebuah gerakan intelektual yang memiliki pengaruh yang signifikan dalam perkembangan pemikiran Islam di Indonesia. Sehingga konsep pembaruan pemikiran yang digagas Nurcholish Madjid (Cak Nur) cenderung hanya dijelaskan secara deskriptif, tanpa meninjau lebih jauh bagaimana nalar yang digunakan dalam mendemonstrasikan pembaruan pemikiran Islam tersebut. Oleh karena itu, artikel ini hendak menganalisis posisi nalar pembaruan pemikiran Islam Cak Nur yang bersumber pada makalah “Keharusan Pembaruan Pemikiran Islam dan Masalah Integrasi Umat” (1970). Metode penelitian yang digunakan ialah studi literatur (library research) dengan pendekatan filosofis-teks. Kemudian, untuk mengidentifikasi posisi nalar Cak Nur, peneliti menggunakan epistemologi nalar Muhammad Abid al-Jabiri. Akhirnya artikel ini menghasilkan kesimpulan, bahwa nalar yang digunakan Cak Nur dalam proyek pembaruan pemikiran Islam lebih condong kepada nalar burhani. Sebab, dalam pembaruan tersebut, Cak Nur menawarkan liberalisasi pemikiran yang meliputi sekularisasi, kebebasan berpikir, ide kemajuan dan sikap terbuka